Perceptions on use of insecticide-treated bed nets to prevent malaria - Magaço, Amílcar (2023)
Funding Information: the authors are grateful to the Mozambican Ministry of Health, to the research assistants who contributed to data collection as well as to the study participants for their dedicated contribution to the study. They would also like to thank the National Malaria Control Programme for its contribution to the planning and implementation of this study. Publisher Copyright: © the Author(s), 2023.